Peran Teknologi Alat Keselamatan Terhadap Kinerja Awak Kapal MV. Mochtar Prabu Mangkunegara - Dedeh Suryani; Lusiani Lusiani (Saintara: Jurnal Ilmiah Ilmu-Ilmu Maritim, 2025)
Safety and crew performance are crucial factors in the operational success of shipping, particularly on the MV. Mochtar Prabu Mangkunegara vessel. This study aims to analyze the impact of safety equipment technology, specifically the Remote Control Life Buoy, on crew performance. The research method used is descriptive quantitative, with data processed from questionnaires and analyzed using Correlation Coefficient and Simple Linear Regression through SPSS. The sample consists of 20 crew members of the MV. Mochtar Prabu Mangkunegara, selected using saturated sampling technique, where all available crew members are included in the study. The results show a strong and positive correlation (r = 0.772) between the role of safety equipment technology and crew performance, where each increase of one unit in the role of safety equipment technology improves crew performance by 0.542 units. The coefficient of determination (R²) of 59.6% indicates that the role of safety equipment technology is a dominant factor influencing crew performance, although 40.4% of other factors also play a role. These findings emphasize the importance of implementing advanced safety technology and providing adequate training to enhance crew performance, which ultimately contributes to improving safety and operational efficiency in shipping.